The conservative treatment of giant omphalocele by tanning with povidone iodine and aqueous 2% eosin solutions. Issue 3 (July 2017) - Habou, Oumarou; Adamou, Harissou; Magagi, Ibrahim Amadou; Ali, Omid M.; Magagi, Amadou; Moustapha, Helle; Sabo, Ramatou; Abarchi, Habibou
Abstract : Aim: The aim of this work was to report the result of nonoperative management of giant omphalocele by dressing with povidone iodine and aqueous eosin in Niger. Patients and methods: This prospective study was conducted over 5 years (January 2011 to December 2015) in the Departments of Pediatric Surgery in the country. The procedure consisted of applying povidone iodine at the initial phase of the treatment as inpatient followed by aqueous eosine solution application as outpatient, which was continued up to complete epidermization. The clinical aspects, the complications and the mortality of omphalocele were discussed. Results: The study included about 13 patients; the mean age at presentation was 1.7 days (range: 3 h–8 days). The delivery was at home in 38.46% of the cases (five out of 13). The average birth weight was 2810 g. Associated congenital abnormalities were found in 46.15% of cases (six out of 13). The mean initial hospitalization duration was 8 days. The average length of complete epidermization duration was 9±2 weeks. The secondary surgical cure was realized in eight patients. The morbidity rate was 30.77% (four out of 13). The mortality rate was 23.07% (three out of 13). Conclusion: The conservative treatment of giant omphalocele through the application of povidone iodine and aqueous eosine is effective and cost-effective. This procedure should be privileged in our limited resources Health centers where pediatric intensive care unit are lacking.